Coaggregation of human oral Cytophaga species and Actinomyces israelii. - Kolenbrander, P E (1983)
A total of 19 strains of oral Cytophaga sp. obtained from subgingival plaque deposits were tested for their ability to coaggregate with strains of Actinomyces israelii, A. viscosus, A. naeslundii, Streptococcus sanguis, S. mutans, S. salivarius, and S. mitis. Coaggregation was observed only with A. israelii. Based on their coaggregation patterns with eight A. israelii strains, the Cytophaga strains were distributed among three distinct groups: those that coaggregated with A. israelii PK16 but not with A. israelii W1011 (ATCC 29322), those that coaggregated with A. israelii ATCC 29322 but not with A. israelii PK16, and those that coaggregated with none of the eight A. israelii strains. In each of the coaggregations, prior heat treatment (85 degrees C, 30 min) of the Cytophaga cells prevented coaggregation, whereas identical treatment of the A. israelii cells had no effect. The ability of A. israelii PK16 to form adherent plaque on a tooth surface previously coated with Cytophaga plaque was tested with one of the coaggregating Cytophaga strains. White patches of A. israelii plaque were found covering both the amber-colored Cytophaga plaque on the cementum surface as well as the enamel surface to which Cytophaga strains do not adhere. Electron micrographs of thin-sectioned mixed-plaque material revealed both cell types in close proximity. In addition, electron micrographs of negatively stained coaggregated cells showed interbacterial adherence between surface fimbrae on A. israelii and outer membrane blebs on the gram-negative Cytophaga sp. The kinetics of binding of A. israelii to spheroidal hydroxyapatite and to root powder were indicative of a high-affinity binding system with comparatively large numbers of available binding sites on both substrata. These results indicate the highly specific nature of Cytophaga sp.--A. israelii recognition. The contribution of such recognition toward the mechanisms that are responsible for the indigenous nature of these oral bacteria is discussed.